A mixed-method study exploring barriers and facilitators to midwives' mental health in Ontario - Elizabeth K. Darling; Lindsay N. Grenier; Rachel K. MacKenzie; Claire Ramlogan-Salanga; Elizabeth C. Cates; Riley Graybrook; Karline Wilson-Mitchell (BMC, 2023)
Abstract Background There is a paucity of information regarding the mental health of midwives working in Ontario, Canada. Many studies have investigated midwives' mental health around the world, but little is known about how the model of midwifery care in Ontario contributes to or negatively impacts midwives' mental health. The aim of the study was to gain a deeper understanding of factors that contribute to and negatively impact Ontario midwives' mental health. Methods We employed a mixed-methods, sequential, exploratory design, which utilized focus groups and individual interviews, followed by an online survey. All midwives in Ontario who had actively practiced within the previous 15 months were eligible to participate. Findings We conducted 6 focus groups and 3 individual interviews, with 24 midwives, and 275 midwives subsequently completed the online survey. We identified four broad factors that impacted midwives' mental health: (1) the nature of midwifery work, (2) the remuneration model, (3) the culture of the profession, and (4) external factors. Discussion Based on our findings and the existing literature, we have five broad recommendations for improving Ontario midwives' mental health: (1) provide a variety of work options for midwives; (2) address the impacts of trauma on midwives; (3) make mental health services tailored for midwives accessible; (4) support healthy midwife-to-midwife relationships; and (5) support improved respect and understanding of midwifery. Conclusion As one of the first comprehensive investigations into midwives' mental health in Ontario, this study highlights factors that contribute negatively to midwives' mental health and offers recommendations for how midwives' mental health can be improved systemically.